(untitled) (Revista Educação Especial em Debate, 2025)
The school caregiver has become a reality, and their importance is linked to changes in the school environment to accommodate students with more severe disabilities, especially in terms of motor abilities. The research question in this study is: what is the conception about the caregiver’s role by general education teachers? Thus, the objective is to analyze the underlying conceptions of regular education teachers about the role of the caregiver in the classroom. Five teachers who worked in a single school in the interior of the state of São Paulo, and who had caregivers and students with disabilities enrolled in their class participated in the study. Data collection was conducted through semi-structured interviews and the content was written in a copybook. Data processing and analysis consisted of identifying the conceptions with the help of two judges who validated the conceptions extracted from the reports. The results indicated that the conceptions about the role of the caregiver is that they are a professional to give assistance to students with disabilities inside and outside the classroom. Emphasis was given by four participants in relation to the caregiver’s role within the classroom, assigning them academic activities, such as reading and writing. In conclusion, the results contrast with the duties for hiring these professionals by municipalities, which would be to take care of issues related to hygiene, feeding, and commuting within the school.